Análise espacial da tuberculose infantil no estado de São Paulo - Carasek, Vinicius Paglione (Universidade Federal de São Carlos, 2023)
INTRODUCTION: Tuberculosis (TB) is a preventable and curable disease, but it continues to impact the lives and development of millions of children and adolescents. Each year, they account for around 11% of all TB cases worldwide, and approximately 1.1 million children and young adolescents under the age of 15 fall ill with TB every year. OBJECTIVES: To analyze the spatial distribution of notified cases of childhood tuberculosis from 2011 to 2022 in the state of São Paulo. METHODS: This is an ecological, descriptive study that used secondary data from notifications of childhood TB cases (<14 years) in the 645 municipalities of the state of São Paulo, which is the most populous state in Brazil. Case data was collected online from the DATASUS/TABNET website and the population was considered according to information from the Brazilian Institute of Geography and Statistics for the 2010 demographic census. To adjust for current data, the percentage of growth was added according to the institute's own population estimates. For better understanding of the occurrence of the event and control of the homogenization of the findings, the data was divided into three time periods: P1 (2011-2014), P2 (2015-2018) and P3 (2019-2022). Descriptive statistics were then analyzed, followed by the application of exploratory spatial analysis called the Global and Local Moran's Index using pre-established neighborhoods to confirm the existence of spatial autocorrelation of the cases. Maps with the spatial association index (LISA) were then constructed using ArcGis software to illustrate the findings. As this is a study involving open access secondary data, there was no need for ethical evaluation. RESULTS: In P1, 1,999 cases of childhood TB in children under 13 were identified in the municipalities of São Paulo; in P2 there were 2,222 cases and in P3 1,806 cases. Spatial autocorrelation was confirmed in all periods using the Global Moran's Index, which showed the following values respectively: P1: 0.166, P2: 0.064 and P3: 0.069. The analysis of the Local Moran's Index, as shown in Figure 1, shows the municipalities with a spatial association between their first-order neighbors according to the period of analysis. CONCLUSION: It was possible to highlight that there is still a high occurrence of childhood TB cases in the state of São Paulo, with heterogeneous distribution and spatial autocorrelation. There are specific municipalities that need to intensify their TB control strategies, due to the fact that the presence of childhood TB cases is an indication that TB control actions in adults are not being carried out effectively enough.
Spatial analysis of childhood tuberculosis in the state of São Paulo
Keywords: Tuberculose; Análise espacial; Geoprocessamento; CIENCIAS DA SAUDE::ENFERMAGEM